Common things : romance and the aesthetics of belonging in Atlantic modernity - Lilley, James D. (James David), 1971- (Commonalities., 2014)
What are the relationships between the books we read and the communities we share? Rooted in an innovative archive of transatlantic materials, this book explores how the romance revivals of the eighteenth and nineteenth century influenced - and were influenced by - emerging modern systems of community.